Transcytosis of T4 Bacteriophage Through Intestinal Cells Enhances Its Immune Activation - Amanda Carroll-Portillo; October Barnes; Cristina N. Coffman; Cody A. Braun; Sudha B. Singh; Henry C. Lin (Viruses)
Interactions between bacteriophages with mammalian immune cells are of great interest and most phages possess at least one molecular pattern (nucleic acid, sugar residue, or protein structure) that is recognizable to the immune system through pathogen associated molecular pattern (PAMP) receptors (i.e., TLRs). Given that phages reside in the same body niches as bacteria, they share the propensity to stimulate or quench immune responses depending on the nature of their interactions with host immune cells. While most in vitro research focuses on the outcomes of direct application of phages to immune cells of interest, the potential impact of their transcytosis through the intestinal barrier has yet to be considered. As transcytosis through intestinal cells is a necessary step in healthy systems for access by phage to the underlying immune cell populations, it is imperative to understand how this step may play a role in immune activation. We compared the activation of macrophages (as measured by TNFα secretion) following direct phage application to those stimulated by incubation with phage transcytosed through a polarized Caco2 epithelial barrier model. Our results demonstrate that phages capable of activating TNFα secretion upon direct contact maintain the stimulatory capability following transcytosis. Furthermore, activation of macrophages by a transcytosed phage is enhanced as compared to that occurring with an equivalent multiplicity of directly applied phage.